EFEKTIVITAS PELAKSANAAN AUDIT MANAJEMEN FUNGSI SUMBER DAYA MANUSIA PADA PT BPR XYZ (PERSERODA) - Isni Maryatun Nur Janah; Tutik Dwi Karyanti; Ardian Widiarto (Gapenas Publisher, 2022)
This study aims to determine the implementation of 11 HR functions and evaluate the effectiveness of HR management at PT BPR XYZ (Perseroda). This research is descriptive qualitative in nature. The population of this study was all employees, totaling 54 people. The sampling technique used is the slovin method, then data collection techniques are carried out by interviews, questionnaires, and documentation. Data analysis uses four stages of management audit consisting of preliminary audits, review, and testing of management controls, detailed audits, and reports. The results of the study show that there are eleven HR functions that have been implemented, including five HR functions that have been running effectively. Meanwhile, the six HR functions that have not been carried out effectively by the company are planning, orientation and placement, training and development, performance appraisal, career development, and employee protection. Recommendations given to increase the effectiveness in managing the company's human resources, namely: 1) establish a detailed and written HR plan. 2) make policies governing orientation and placement. 3) make an evaluation of the implementation of the training program. 4) conducting open performance appraisals, 5) making detailed regulations regarding promotions and demotions, and 6) establishing a hazard early warning system and providing first aid training to employees